UJI EFEKTIVITAS SEDIAAN PATCH EKSTRAK DAUN CENGKEH (Syzygium aromaticum) SEBAGAI REPELLENT NYAMUK - Sy. Pakaya, M.Si.,Apt, Mahdalena; Thomas, Nurain; Arista Idris, Pinkan (State University of Gorontalo, 2019)
Clove (Syzygium aromaticumL.) leaf has efficacy as repellent because it contains terpenoid eugenol. This study aimed to determine how the effectiveness of clove leaf extract patch dosage as a mosquito repellent. This research was started with extraction using maceration method with 96% ethanol solvent. Furthermore, making the dosage of patch of clove leaf extract using matrix method with variation of the clove leaf extract concentration. Then, the effectiveness of mosquito repellent patch was tested by using rabbit that divided into 5 treatment groups namely K- (base patch), K+ (mosquito repellent patch), 3 groups of clove leaf extract patch with variation of concentration of F1a (concentration of 1%), F1b (concentration of 3%), and F1c (concentration of 5%). Each group was attached to the clothes of the rabbit and put into the experimental box that had been put by mosquito as many as 20 tails. Based on result of ANNOVA statistic test showed that clove (Syzygium aromaticumL.) leaf patch dosage against the rabbit gave a significant effect against mosquito repellent, where at 5% concentration of clove leaf extract could give mosquito repellent efficacy better than concentration 1% and 3%.